Capacitation of ATER agents: training processes in agroecology in the Southeast of Brazil (Research, Society and Development, 2021)
This article aims to bring reflections on the training of professionals in the field of agroecology to work in the Technical Assistance and Rural Extension (ATER) services based on a new socio-technical perspective. For this, field research was carried out between the years 2016 to 2018 focusing on professionals linked to public institutions and social organizations working in the provision of ATER services in the states of the Southeast Region of Brazil (Rio de Janeiro, Espírito Santo, Minas Gerais and São Paulo). The authors resort to a debate on Rural Extension and its connections with the transition to agroecology as one of its fundamental principles, incorporated into the National Policy for Technical Assistance and Rural Extension (PNATER) even though relativized by Law 12.188 / 2010, which adopted the term ecologically based agriculture to replace agroecological bias. The results achieved through the different training strategies implemented in the studied region are presented and discussed in detail. Regarding the training of Ater agents in the context of Agroecology, it was observed that this framework is treated as a scientific, lively, interactive and challenged approach, which seeks to recognize in its protagonists, especially in family farmers and their organizations, an important role for the rural development of the Brazilian countryside.